Level Attacks of Slender Rice Bug (Leptocorisa oratorius) in Tanah Miring District, Merauke Regency Papua - Sembiring, Jefri; Sarijan, Abdullah; Katmok, Bonefasius; Mendes, Johanna (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2022)
The slender rice bug (Leptocorisa oratorius) is an important pest in Merauke Regency because it can cause a decrease in rice production. Rice plants that are attacked by this pest will produce rice with poor quality, because the color becomes black spots and can calcify. This study aims to determine the level of attack and population density of L. oratorius in the Tanah Miring Merauke District, Papua Province. The method used in this research was purposive sampling. Determination of sampling locations by selecting a paddy field with a minimum size of 1250 m2 on one rice field per variety, then determining 9 sampling points. Sampling of the slender rice bug used an insect net with a diameter of 40 cm which was carried out in 1 double swing at each point measuring 1 x 1 m. The results showed that the average intensity of damage caused by stink bugs in Tanah Miring District was 13.78%. The highest average population density was in Waninggap Miraf village with 46.6 individuals, Yasamulya village, Isanombias village with 44.33 individuals, Yabamaru village with 38.66 individuals, Bersehati village with 38.33 and the lowest was Amunkay village with 30 individuals. While the population average in each observation was highest in the second observation or 55 HST of 46.4 individuals followed by the first observation or 45 HST of 37.4 individuals and the last observation or 65 HST of 29.8 individuals. The most preferred type of variety by the stink bug was Impari 32 (19.76%). Monitoring the development of the slender rice bug population is necessary to prevent the possibility of a population explosion so that it can be controlled earlier.